2016
DOI: 10.1186/s13045-016-0363-1
|View full text |Cite
|
Sign up to set email alerts
|

High rate of complete responses to immune checkpoint inhibitors in patients with relapsed or refractory Hodgkin lymphoma previously exposed to epigenetic therapy

Abstract: Options for patients with relapsed or refractory (R/R) classical Hodgkin lymphoma (cHL) after brentuximab vedotin (Bv) and autologous stem cell transplantation (ASCT) are limited. Immune checkpoint inhibitors (ICI) are active in this population but rarely induce complete response (CR). Ten patients with R/R cHL after ASCT and Bv received pembrolizumab (n = 8) or nivolumab (n = 2). Five had been previously exposed to 5-azacitidine on a phase 1 study. Among nine evaluable patients, seven (78%) achieved CR, one p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…Within a small cohort of patients previously treated with hypomethylating agents on a phase I clinical trial for classical Hodgkin lymphoma, there was observed benefit in later response to subsequent treatment with immune checkpoint inhibitors [24], although the trial was not powered to determine effacacy. All patients within the cohort had been heavily treated for relapsed/refractory Hodgkin lymphoma, including brentuximab vedotin and/or autologous stem cell transplantation, prior to receiving immune checkpoint therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Within a small cohort of patients previously treated with hypomethylating agents on a phase I clinical trial for classical Hodgkin lymphoma, there was observed benefit in later response to subsequent treatment with immune checkpoint inhibitors [24], although the trial was not powered to determine effacacy. All patients within the cohort had been heavily treated for relapsed/refractory Hodgkin lymphoma, including brentuximab vedotin and/or autologous stem cell transplantation, prior to receiving immune checkpoint therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In the earliest phase of clinical introduction of checkpoint inhibitors in 'real-world' practice, Falchi and colleagues suggested the potential favorable role of hypomethylating agent 5-azacitidine on checkpoint blockade response through a synergistic priming effect on the immune system. 181 Later, in a phase II study of 86 rr-cHL patients who had received at least two lines of previous therapy, the addition of low-dose decitabine to the checkpoint inhibitor camrelizumab led to higher CR rates in anti-PD1-naïve patients that reached 71% versus 32% in the anti-PD1 monotherapy arm. The study revealed the potential of the combination to induce responses in patients who had been previously refractory to PD1 inhibition.…”
Section: Brentuximab Vedotin As Salvage Therapy For Relapsed/refractomentioning
confidence: 99%
“…Currently, pembrolizumab has FDA approved indications of seven different types of advanced malignancies. These malignancies include melanoma [ 39 , 40 ], NSCLC [ 41 44 ], HNSCC, urothelial carcinoma, Hodgkin’s lymphoma [ 45 ], and gastric cancer [ 46 , 47 ] (Table 1 ). Among these, FDA approved one indication for any malignancy with high microsatellite instability or mismatch repair gene (MMR) deficiency [ 48 ].…”
Section: New Development In Clinical Applications Of Pd-1 and Pd-l1 Amentioning
confidence: 99%